Quantitative dynamics of foot-and-mouth disease virus infection in pigs - Quan, Melvyn (The University of Edinburgh, 2005)
Foot-and-mouth disease (FMD) is caused by the foot-and-mouth disease virus (FMDV), genus Aphthovirus, family Picornaviridae. It is a highly contagious disease of cloven-hoofed animals, has a worldwide distribution and plays an important role in the limitation of international trade in livestock and livestock products.

The main objectives of this project were to provide an accurate quantitative description, and develop a mathematical model, of FMDV dynamics in infected pigs. Time-course studies were set up and the viral load in serum, nasal swabs and tissue samples were determined. Time after infection, mode of infection, inoculation dose and housing conditions were examined as possible determinants of viral load.

Similar results were obtained from pigs infected with FMDV by the intravenous, intradermal or oro-nasal route, i) A strong relationship between inoculation dose and incubation period of FMDV was evident: the higher the inoculation dose, the shorter the incubation period, and vice versa, ii) The higher the inoculation dose, the more predictable and consistent was the incubation period and time-course of infection. The lower the inoculation dose, the more variable was the incubation period and the probability of subclinical infections, iii) Housing pigs in a group (rather than individually) resulted in synchronous infections and reduced the variance in the incubation period.

Initial models of the early viral dynamics of FMDV disagreed with the experimental data. Experimental data showed larger effects of dose on the temporal distribution of viraemia than was predicted by the models. This disagreement could be resolved by: i) limiting the rate of infection of epithelial cells at low FMDV concentrations; ii) converting the virus removal system (such as the mononuclear phagocyte system) into one of limited capacity; or iii) the addition of a virus removal system of limited capacity, such as non-specific binding of FMDV into the models.

A hypothesis in which the rate of infection of epithelial cells was limited at low FMDV concentration could be supported by the literature. For FMDV to successfully infect and replicate within a cell, host protein synthesis has to be inhibited and anti¬ viral defences inactivated. The probability of a successful infection of a cell increases as the number of infecting viruses increases, suggesting that the rate of infection of cells at low FMDV concentrations is indeed limited.

The experimental work has highlighted the strong relationship between inoculation dose and dynamics of FMDV in vivo and the modelling exercise has highlighted important determinants of viral dynamics, as well as areas where further research should be directed. This has lead to a deeper understanding of the dynamics of, not only FMDV, but virus infections in general.